2019
DOI: 10.1038/s41598-019-45130-1
|View full text |Cite
|
Sign up to set email alerts
|

All-Male Groups in Asian Elephants: A Novel, Adaptive Social Strategy in Increasingly Anthropogenic Landscapes of Southern India

Abstract: Male Asian elephants are known to adopt a high-risk high-gain foraging strategy by venturing into agricultural areas and feeding on nutritious crops in order to improve their reproductive fitness. We hypothesised that the high risks to survival posed by increasingly urbanising and often unpredictable production landscapes may necessitate the emergence of behavioural strategies that allow male elephants to persist in such landscapes. Using 1445 photographic records of 248 uniquely identified male Asian elephant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Our results indicated no effect of elephant group size, all‐male groups, or the proportion of the moon illuminated on the likelihood of elephants crossing the fence. This contrasts with studies that found crop damage to be more prevalent in relatively smaller groups (King et al, 2017; Kioko et al, 2006) and all‐male or male‐dominated groups (Srinivasaiah, Kumar, Vaidyanathan, Sukumar, & Sinha, 2019). Interestingly, compared to similar studies (e.g., King et al, 2017), we observed larger breeding herds near the beehive fence.…”
Section: Discussionmentioning
confidence: 68%
“…Our results indicated no effect of elephant group size, all‐male groups, or the proportion of the moon illuminated on the likelihood of elephants crossing the fence. This contrasts with studies that found crop damage to be more prevalent in relatively smaller groups (King et al, 2017; Kioko et al, 2006) and all‐male or male‐dominated groups (Srinivasaiah, Kumar, Vaidyanathan, Sukumar, & Sinha, 2019). Interestingly, compared to similar studies (e.g., King et al, 2017), we observed larger breeding herds near the beehive fence.…”
Section: Discussionmentioning
confidence: 68%
“…Notably, the recent proliferation of hakkapatas is concerning. These explosives disproportionately affect subadult male elephants, perhaps because this demographic is more likely to explore new areas and occupy low-quality habitat (Srinivasaiah et al 2019). Given their propensity to engage in crop-raiding, research on the ecology of male elephants in particular could assist with management strategies, lending insight into the environmental and behavioral motivation to engage in HEC (Srinivasaiah et al 2012, Mumby andPlotnik 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a higher body condition of adult males than adult females. This may be because adult males are known to have larger home ranges than adult females [74,81], and are more tolerant to human disturbance [82]. This means they can more frequently forage in areas near the reserve boundary, where intensive anthropogenic activities like hunting, grazing, fishing and collecting mushrooms have also been recorded by cameras.…”
Section: Health Conditionmentioning
confidence: 99%